Tuning the Mechanical and Electrical Properties of Stretchable PEDOT:PSS/Ionic Liquid Conductors. Issue 23 (12th November 2020) - Kee, Seyoung; Kim, Nara; Park, Hyunmin; Kim, Bong Seong; Teo, Mei Ying; Lee, Seongyu; Kim, Jehan; Lee, Kwanghee
Abstract: Conducting polymers (CPs) constitute a promising building block to establish next‐generation stretchable electronics. However, achieving CPs with both high electrical conductivity and outstanding mechanical stretchability beyond flexibility is still a major challenge. Therefore, understanding the key factors controlling such characteristics of CPs is required. Herein, a method to simultaneously manipulate the mechanical and electrical properties of a representative CP, PEDOT:PSS, by modifying ionic liquid (IL) additives is reported. The cation/anion modification of ILs distinctly improves the electrical conductivity of PEDOT:PSS up to ≈1075 S cm −1, and the PEDOT:PSS/IL films showing higher conductivity also exhibit superior electromechanical stretchability, enabling them to maintain their initial conductivity under a tensile strain of 80%. Based on grazing incidence wide angle X‐ray scattering and Fourier transform infrared spectroscopy analyses, it is found that the cation/anion‐modified ILs control the crystallinity and π–π stacking density of conjugated PEDOT chains and the growth of amorphous PSS domains via IL‐induced phase separation between PEDOT and PSS, which can be the origin of the significant conductivity and stretchability improvements in PEDOT:PSS/IL composites. This study provides guidance to develop highly stretchable CP‐based conductors/electrodes. Abstract : The mechanical and electrical characteristics of PEDOT:PSS can be simultaneously manipulated via modification of ionic liquid (IL) additives. The cation/anion‐modified ILs control the growth of amorphous PSS domains and crystallinity of π‐conjugated PEDOT chains, which allows the PEDOT:PSS/IL films to provide high electrical conductivity (≈1075 S cm −1 ) and superior electromechanical stretchability while maintaining initial conductivity under strain up to 80%.